Respuesta :

f(x)+g(x) = 3 / 5x + (-3x / 2)
f(x)+g(x) = (6 - 15x^2) / (10x)
f(x)+g(x) = (15x^2 - 6) (-10x)

Answer is D. 
Hope it helps
kanest
Replace f(x) and g(x) with what they equal:

[tex]\frac{3}{5x} - \frac{3x}{2}[/tex]

The formula for subtracting equations is given out by the following expression:

[tex] \frac{a}{b} - \frac{c}{d} = \frac{ad-bc}{bd}[/tex]

Plug the values in the equation in this formula:

[tex]a = 3, b = 5x, c = 3x, d = 2[/tex]

[tex] \frac{(3 \times 2) - (5x \times 3x)}{(5x \times 2)} = \frac{6 - 15x^{2}}{10x}[/tex]

You can transfer positives and negatives from the numerator to the denominator by multiplying each term by -1, as they will equal the same:

[tex]\frac{-15x^{2} + 6}{10x} \times \frac{-1}{-1} = \frac{15x^{2} - 6}{-10x}[/tex]

The answer is D.
ACCESS MORE